Factors Determining Student Engagement in Learning English as a Foreign Language (EFL) - Nieścioruk, Julia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents how selected individual factors influence student engagement in learning English as a foreign language (EFL). It emphasises the role of student`s interpersonal relationships with their environment and other participants of the educational process, and their influence on the quality of received language education. The concluding paragraph proposes solutions for encouraging and managing student engagement during EFL classes as well as suggestions concerning the creation of suitable, safe, and encouraging classroom environment for the fruitful development of student`s foreign language proficiency. The paper concludes with a statement concerning the role of an educator/teacher and their support in the process of teaching English as a foreign language (TEFL).
Keywords: nauczanie języka angielskiego jako języka obcego (TEFL); czynniki wpływające na zaangażowanie uczniów; angażujące metody nauczania języków obcych; zmienne osobowościowe; teaching English as a foreign language (TEFL); factors influencing student engagement; engaging methods of teaching foreign languages; personality variables